"Traditional Architecture of Uzbekistan: Passive Solar Heating and Climate Adaptation" (Journal of Architectural Design, 2025)
Already at the early stages of the development of human society, architecture was closely connected with the climate and natural environment. Man was forced to solve construction problems put forward by climatic conditions at the site of the construction of structures. For example, Vitruvius (I century BC) in his work "Ten Books on Architecture" wrote that buildings in their style, obviously, should be different in their style, in Egypt and Spain, in Pontus and Rome and in countries and regions differing in characteristic features. For one part of the earth lies directly under the sun, another is far from it, and a third is exposed to it at a moderate distance